VARIASI PERTUMBUHAN TINGGI KLON HIBRID Acacia (A. mangium x A. auriculiformis) UMUR 12 BULAN DI WONOGIRI, JAWA TENGAH - Sri Sunarti; Muhammad Na'iem; Eko Bhakti Hardiyanto; Sapto Indrioko (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2013)
Forty four clones of Acacia hybrid propagated from selected stoolplants were tested together with a control of pure species seedling and clone in a clonal test established at Wonogiri, Central Java. The design of clonal test was Incomplete Block Design, which was laid-out as single treeplot of 20 replications with spacing of 3 m x 3 m. Measurements of tree height were conducted at age 12 months. There were significant differences between the clones in height growth. Eleven clones of 44 were more superior than the original population at SSO F1 (Control 4th) which superiority ranging from 1.81-35.35 % and 3 of them were more superior than the pure species (control 1th, control 2th and control 3th) which superiority ranging from 3.51 – 17.28%. Meanhile, clone repeatability for height at age 12 months was, while individual repeatability for height was 0.59 +- 0.1